Role of MicroRNA-1 in Human Cancer and Its Therapeutic Potentials. (18th May 2014) - Han, Chao; Yu, Zujiang; Duan, Zhenfeng; Kan, Quancheng
Abstract : While the mechanisms of human cancer development are not fully understood, evidence of microRNA (miRNA, miR) dysregulation has been reported in many human diseases, including cancer. miRs are small noncoding RNA molecules that regulate posttranscriptional gene expression by binding to complementary sequences in the specific region of gene mRNAs, resulting in downregulation of gene expression. Not only are certain miRs consistently dysregulated across many cancers, but they also play critical roles in many aspects of cell growth, proliferation, metastasis, apoptosis, and drug resistance. Recent studies from our group and others revealed that miR-1 is frequently downregulated in various types of cancer. Through targeting multiple oncogenes and oncogenic pathways, miR-1 has been demonstrated to be a tumor suppressor gene that represses cancer cell proliferation and metastasis and promotes apoptosis by ectopic expression. In this review, we highlight recent findings on the aberrant expression and functional significance of miR-1 in human cancers and emphasize its significant values for therapeutic potentials.